Situs Bawahparit: Jejak Penguburan Masa Transisi - Lutfi Yondri (Jurnal Lektur Keagamaan, 2014)
Burial is one of some activities in human life, which have been doing  if someone died. In Indonesia, before the arrival of Islamic influence, the prehistoric people had been practiced the buried activity. And then it have been develop and change. In other site, on the burial site sometime has the indication with two signs; prehistoric and Islamic burial. That facts, we can find in Bawahparit site that have location on Kototinggi District, Limapuluhkoto regent’s, West Sumatera.  After we find a hundred up right stones standing on site’s surface, came through excavation we had founded human skeleton from last buried. Those skeletons are setting down in cavity like on grave cavity. It’s putting down in northwest-southeast orientation. Are the burial coming from prehistoric era, Islamic era, or its coming from the transition era? Through the archeological studies, It‘s a problem try to described, analyzed and solved on this paper. Keywords: Site, burial, culture, transition era